PENGEMBANGAN SARANA PRASARANA DASAR WISATA BENDUNGAN PABELAN - Ahmad Zaki; Seplika Yadi; Tri Wahyono; Fatha Ludfi Alfa'izun (LPPM Universitas Abdurrab, 2022)
The Sabo Dam (Dam) of the Pabelan River, as a water system infrastructure for agricultural land, has the potential to be used by the community as a tourist destination. Since being built in 2018, the Pabelan River dam area has not been used for activities other than irrigation. The area has enormous potential if it is used as a tourist destination. The use of the dam area as a tourist attraction is considered very appropriate, considering the Pabelan Village area is the entrance area for the international tourist area of Borobudur Temple. This is a huge advantage and potential, especially in introducing new tourist destinations to the public. The Sabo Dam Sungai Pabelan tourist attraction can be developed into several types of tourism, such as jeep adventure tours, camping grounds, educational tours, and outbound. But the problem is that there is no supporting infrastructure now. Two-wheeled vehicles can only traverse the road or access this dam. In fact, one or two points are rather difficult for two-wheeled vehicles to pass, and one must be careful. Infrastructure facilities are needed because they will facilitate and provide comfort for visitors to visit the dam tourist attraction. The solution offered to solve the problems faced is revitalizing dam tourism infrastructure by designing infrastructure that supports dam tourism. The partner of this service activity is the Karang Taruna Pabelan Village. The target is the existence of a blueprint for dam tourism infrastructure, which is achieved by designing with Google Sketch Up which begins with surveys and measurements of service locations.